2000
DOI: 10.1177/074193250002100303
|View full text |Cite
|
Sign up to set email alerts
|

Charter Schools and Students with Disabilities

Abstract: Currently, charter school laws exist in 30 states, and more than 1,000 charter schools are now in operation (Center for Education Reform, 1998). The rapid increase in the number of charter schools suggests that this educational reform may have the potential to become a major factor in the education of U.S. children. Charter schools are serving a variety of students, and recent studies at the national level show that a sizable proportion of students being served in charter schools have disabilities. Yet few stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Having close contact with the parents and informing them about their child's improvement in each stage is considered one of the most important roles of the special education teacher. The results are consistent with those of Bairat (2005), Bairat and Al-Zeraiqat (2012), Lange and Lehr (2000), Siebes (2006), Campbell (1995), Larter (1986, and Phillips (1990).…”
Section: -Services Related To the Means And Methods Usedsupporting
confidence: 82%
“…Having close contact with the parents and informing them about their child's improvement in each stage is considered one of the most important roles of the special education teacher. The results are consistent with those of Bairat (2005), Bairat and Al-Zeraiqat (2012), Lange and Lehr (2000), Siebes (2006), Campbell (1995), Larter (1986, and Phillips (1990).…”
Section: -Services Related To the Means And Methods Usedsupporting
confidence: 82%
“…When reviewing for threats-to-validity, two reports, Scott and Government Accountability Office (2012) and Winters et al (2013), did not provide enough information to determine if there was statistical conclusion validity. Three reports, Lake et al (2012), Winters et al (2013Winters et al ( , 2014, of the eight self/third-party reports contained external validity threats regarding population generalization, as they reviewed data limited to a single state, city, or school district. Five of the reports utilized national data and were not deemed to have a population generalization validity threat.…”
Section: Results From the Self/third-party Reportsmentioning
confidence: 99%
“…Five of the reports indicated that students with disabilities were enrolled in charter schools at a lower rate than the traditional public schools in their study location. One report noted that enrollment of students with disabilities at middle and high school charters were indistinguishable from traditional public schools in their study location and that only charter elementary schools showed under enrollment of students with disabilities (Lake et al, 2012). Instead of spending time illustrating the data for the enrollment rates, many of the reports devoted significant time further disaggregating enrollment data to determine why there was a gap in enrollment of students with disabilities between charter schools and traditional public schools.…”
Section: Results From the Self/third-party Reportsmentioning
confidence: 99%
“…Despite taking an important place in the marketing of schools, most schools provide almost no information about specific facilities and very limited information about the accessibility, adaptability and friendliness of the school-facilities for students in need of special support. Schools facilities that are adapted or friendly to consumers in need of special support is an important part of the information these consumers seek when they make school choice (Bajwa-Patel and Devecchi, 2014; Lange and Lehr, 2000; Tah, 2019; Weidner and Herrington, 2006). The marketing information failure to inform about the adaptability and friendliness of the schools’ facilities lacks specific appeal to students in need of special support.…”
Section: Methods and Programmesmentioning
confidence: 99%